2014
DOI: 10.1007/s00404-014-3262-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined oral prednisolone and heparin versus heparin: the effect on peripheral NK cells and clinical outcome in patients with unexplained recurrent miscarriage. A double-blind placebo randomized controlled trial

Abstract: PurposeTo evaluate the efficacy of the use of oral Prednisolone and heparin versus the use of heparin alone in treatment of patients with unexplained recurrent miscarriage.MethodologyThe study was a double-blind placebo randomized control trial conducted on 160 patients with unexplained recurrent miscarriage. Patients recruited were randomized into two groups. The first group received oral Prednisolone in addition to low dose aspirin and heparin, while the other group received a placebo in addition to low dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 24 publications
2
42
0
1
Order By: Relevance
“…121 Authors suggested a suppressive effect of steroids on the peripheral NK cells concentration in women with unexplained RM. 122 However, a study published by Tang et al on the use of prednisolone in patients with high levels of uterine NK (uNK) cells suggested that live birth rate among the prednisolone group was 60% and among the placebo group it was 40% with a risk ratio of 1.5, and hence non-significant. 123 The discrepancy between these data may be due to the sample size and the beginning of treatment.…”
Section: Therapeutical Insights and Future Directionsmentioning
confidence: 97%
See 1 more Smart Citation
“…121 Authors suggested a suppressive effect of steroids on the peripheral NK cells concentration in women with unexplained RM. 122 However, a study published by Tang et al on the use of prednisolone in patients with high levels of uterine NK (uNK) cells suggested that live birth rate among the prednisolone group was 60% and among the placebo group it was 40% with a risk ratio of 1.5, and hence non-significant. 123 The discrepancy between these data may be due to the sample size and the beginning of treatment.…”
Section: Therapeutical Insights and Future Directionsmentioning
confidence: 97%
“…123 The discrepancy between these data may be due to the sample size and the beginning of treatment. 122 The role of the low dose aspirin (LDA) in treatment strategies of obstetrical syndromes has been investigated. 124,125 Acetylsalicylic acid has non-platelet-mediated effects that contribute to its efficacy in the primary and secondary prevention of cardiovascular events.…”
Section: Therapeutical Insights and Future Directionsmentioning
confidence: 99%
“…Prednisolone effectively reduces the number of uterine NK cells in women with RPL and is the most widely used in this patient population 126. Some studies showed an improvement in LBR when prednisolone was combined with aspirin or LMWH,127,128 whereas others showed no effect 41. Moreover, the safety of corticosteroid treatment in the first trimester is still under scrutiny, with some studies showing an increased risk of prematurity, as well as maternal hypertension and diabetes 41,129.…”
Section: Unexplained Rpl (Urpl)mentioning
confidence: 99%
“…For the 85 remaining articles, the full texts were examined carefully on the bases of both inclusion and exclusion criteria, and 36 studies were excluded due to unavailable data, lack of intervention group, or small sample size. Finally, results from 49 literatures were selected for further analysis . The process is displayed in a flowchart in Figure .…”
Section: Resultsmentioning
confidence: 99%